Liver Steatosis: Better Predictor of CKD in MAFLD Than Liver Fibrosis as Determined by Transient Elastography With Controlled Attenuation Parameter - Marc, Luciana; Mihaescu, Adelina; Lupusoru, Raluca; Grosu, Iulia; Gadalean, Florica; Bob, Flaviu; Chisavu, Lazar; Olariu, Nicu; Tucicovschi, Vlad; Timar, Bogdan; Sporea, Ioan; Timar, Romulus; et al. (Frontiers in Medicine, 2022)
Background: Changing the term/concept of NAFLD to MAFLD (metabolic dysfunction associated fatty liver disease) broadens the pathological definition to include chronic renal involvement and possibly changes CKD's epidemiological association with liver disease. Our study explores the relationship between MAFLD and CKD using TE with CAP. Methods: We evaluated 402 diabetic patients with MAFLD and high CKD risk using TE with CAP (FibroScan®). CKD was defined according to Kidney Disease Improving Global Outcomes (KDIGO)2012 guidelines. Logistic regression and stepwise multiple logistic regression were used to evaluate the factors associated with CKD. In addition, ROC analysis was used to assess the performance of CAP and TE in predicting CKD. Results: The prevalence of CKD in our group was 60.8%. Patients with CKD had higher mean LSM and CAP values than those without CKD. We found that hepatic steatosis was a better predictor of CKD than was fibrosis. Univariate regression showed that CAP values >353 dB/m were predictive of CKD, and multivariate regression analysis (after adjustment according to sex, BMI, LDLc, HDLc, and fasting glucose) showed that CAP values >353 dB/m were more strongly associated with the presence of CKD compared to LSM (fibrosis) values. Conclusion: In patients with MAFLD, CAP-assessed steatosis appears to be a better predictor of CKD compared to LSM-assessed hepatic fibrosis.